Evaluating the significance of level IIb neck dissection for hypopharyngeal cancer. Issue 12 (18th March 2013) - Sakai, Akihiro; Okami, Kenji; Sugimoto, Ryousuke; Ebisumoto, Koji; Yamamoto, Hikaru; Maki, Daisuke; Atsumi, Taku; Saito, Kosuke; Iida, Masahiro
<x xml:space="preserve">Abstract</x> Background This study evaluated cervical lymph node metastases at level IIb in cases of hypopharyngeal cancer and analyzed the possibility of preservation of level IIb during neck dissection. Methods In total, 34 patients (51 neck sides) with hypopharyngeal cancer that underwent neck dissection from April 2008 to April 2011 were retrospectively analyzed. We evaluated the distribution of metastatic lymph nodes at various levels (particularly level IIb) in cases treated with therapeutic neck dissection and elective neck dissection. Results The incidence of metastases in level IIb was 13.3% (4 of 30 patients) for therapeutic neck dissection and 0% (0 of 21 patients) for elective neck dissection. All the level IIb metastases were found on the ipsilateral side in the cases treated with therapeutic neck dissection. Conclusions The results suggest that preservation of level IIb during neck dissection was possible in N0 cases of hypopharyngeal cancer. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1777–1780, 2013